ANALISIS KUAT GESER LANGSUNG TANAH PADA TPA KUDUS YANG TERNORMALISASI - Rizka Silviana Hartanti; Masturi Masturi; Ian Yulianti (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
Final Disposal (TPA) is a disposal of the remains (garbage) activities of residents of organic to inorganic. Trash that has fulfilled the land will be relocated to another place so that the former is called the normalized TPA or the land back to the beginning of the function. The purpose of this study was to determine the direct shear test of TPA in the district of Kudus normalized to determine the water content test and direct shear strength test soil with soil variations normalized landfill and landfill soil that has not been normalized. The method used is to take soil samples tested in the laboratory and continued with retrieval data retrieval. Data were analyzed using 1D graph. Having done the research results that the water content in the TPA normalized ie 34,23% while the landfill soil that has not been normalized with 33,15%. To test the shear strength obtained TPA normalized graph of normal stress to shear stress resulting friction angle value 19,070 and the value of cohesion (c) 8561,7N/m2. To test the shear strength normalized landfill that has not obtained a graph of normal stress to shear stress resulting friction angle value 22,850 and the value of cohesion (c) 6429,9N/m2. Key words: land, landfills (TPA), normalized, direct shear test.